Applications of carbon quantum dots (CQDs) in membrane technologies: A review - Zhao, Die Ling; Chung, Tai-Shung (Water research (Oxford), 2018)
Carbon quantum dots (CQDs), which are a fascinating class of nanostructured carbons, have recently attracted extensive attention in the field of membrane technologies for their applications in separation processes. This is because they possess two unique advantages. Their productions are facile and inexpensive, while their physicochemical properties such as ultra-small sizes, good biocompatibility, high chemical inertness, tunable hydrophilicity, rich surface functional groups and antifouling characteristics are highly desirable. Leveraging on these, researchers have explored their utilizations in various membrane designs for reverse osmosis (RO), ultrafiltration (UF), nanofiltration (NF), forward osmosis (FO), pressure retarded osmosis (PRO), membrane distillation (MD), and organic solvent nanofiltration (OSN) processes. In particular, CQDs have especially stimulated exploration in the field of water treatment by membrane technologies since biocompatibility of membrane materials is of utmost importance to ensure safety of drinking water. In addition, CQDs are in a favorable position for achieving unprecedented performance of membrane separation processes in water treatment, in the light of substantial efficiency enhancement and antifouling propensity as discovered in recent studies. In this article, we will review the progress in the development of CQD incorporated membranes with discussions on their challenges and perspectives. [Display omitted] •The state-of-the-art of CQD modified membranes for different applications are summarized.•The methods to incorporate CQDs into membranes are introduced.•The challenges and future of CQDs for membrane technologies are elaborated.